The Effect of User Interface, User Experience, and Service Quality on Customer Satisfaction of Generation Z Using Ollin Mobile Banking by Bank Nagari in Padang City - Ilham, Aulia Puja (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the factors influencing customer satisfaction among Generation Z users of the Ollin mobile banking service by Bank Nagari in Padang City. The research focuses on three key variables: User Interface/UI, User Experience/UX, and Service Quality. Using a quantitative approach with Ordinary Least Squares (OLS), the study involved 100 respondents aged 15–26 years in Padang City. The findings reveal that, individually, User Interface and Service Quality have a positive and significant impact on customer satisfaction, highlighting their critical role in enhancing user experience. In contrast, User Experience shows a positive but statistically insignificant effect. When examined simultaneously, all three variables, UI, UX, and Service Quality, positively influence customer satisfaction, indicating that their combined effect can improve overall satisfaction among Generation Z users. These results underscore the importance of a well-designed interface and high-quality service in meeting the expectations of digital banking customers.